Strategi Komunikasi Dinas Kependudukan dan Catatan Sipil dalam Pelayanan Administrasi Kependudukan melalui Program BERLAYAR di Kabupaten Batu Bara - Riska Putri Nasution (Universitas Muhammadiyah Sumatera Utara, 2026)
Civil registration services are public services that play a crucial role in ensuring the legal identity of citizens and meeting other service needs. In practice, civil registration services still face challenges such as limited access to services, geographical conditions of the region, and the public’s low understanding of the importance of civil registration documents. As a solution, the Batu Bara Regency Government launched the BERLAYAR Program (Regent’s Synergy in Serving the Community) to bring services closer to the public. However, the effectiveness of this program heavily depends on communication strategies to ensure service information is conveyed optimally. This study examines the communication strategies of the Batu Bara Regency Population and Civil Registry Office in providing population administration services through the BERLAYAR Program. This study employs a qualitative descriptive research design. Data were collected through interviews, observations, and documentation involving functional officials, field staff, and the public as service recipients. The results indicate that communication strategies within the BERLAYAR Program are implemented through the stages of research, planning, implementation, evaluation, and reporting. Information dissemination is carried out through interagency coordination, the use of social media, and direct face-to-face communication with the public. This communication strategy helps make it easier for the public to access civil registration services and increases public awareness of the importance of civil registration documents.